(untitled) (Acta Scientiarum. Health Sciences, 2020)
The aim of the study was to investigate the association between different anthropometric indicators and high blood pressure in adults with obesity.This is a cross-sectional study with a non-probabilistic sample of adults with obesity. Systolic and diastolic blood pressure were measured using automated equipment (OMRON, model 742 HEM). The anthropometric indicators used were body mass index (BMI), relative fat mass (RFM), waist circumference (WC), waist-to-stature ratio (WSR) and waist-hip ratio (WHR). The data were analyzed by crude and adjusted (sex and age) linear regression, adopting a level of significance p <0.05. Among the 63 adults with obesity evaluated (38 woman; 35.27±7.02 years; BMI: 33.46±2.89 kg m-2; RFM: 39.98±6.70; WC: 109.38±10.15 cm; WSR: 0.64±0.05; WHR: 0.93±0.01), it was observed that the increase in systolic blood pressure was directly associated with the indicators RFM (p=0.011; Cohen’s F²= 0.42), WC (p=0.003; Cohen’s F²= 0.49), WSR (p=0.010; Cohen’s F²= 0.42) e WHR (p=0.001; Cohen’s F²= 0.52), but not to BMI (p=0.100). The elevation of diastolic blood pressure was directly associated with all the anthropometric indicators analyzed: BMI (p=0.040; Cohen’s F²= 0.14), RFM (p= 0.006; Cohen’s F²= 0.21), WC (p=0.002; Cohen’s F²= 0.26),WSR (p=0.004 Cohen’s F²=0.23) and WHR (p=0.012; Cohen’s F²=0.19). It was concluded blood pressure elevation was directly associated with the anthropometric indicators investigated and, among them, the WHR and the WC presented the best predictive capacity for systolic blood pressure and diastolic blood pressure elevations, respectively